«Unstoppable Together». Gender, Class and Feminism in Nike’s commercial strategies in Argentina - Álvarez Litke, Martín (2020)
In the framework of the expansion of feminisms, we attend to the proliferation of advertisements that (re)produce androcentric views on the new ways of being woman, aligned to the imaginary of contemporary active life that the market wants to exalt, display, promote and propagate. We start by thinking of advertising as «gender technologies» (De Lauretis, 1989) to analyze the commercial strategy of the American brand Nike, leader in the sports market. Currently, the company complements its advertisements with a presence in the field and on social networks, seeking to expand its impact network and thus reach different consumers. In this article we question the ways in which Nike seeks to engage women in multiple scenarios, and investigate the consequences that the brand’s practices have on the subjectivity and materiality of athletes. To do this, we reflect on our ethnographic records on running and football practiced by women in different contexts in the city of Buenos Aires (Argentina), and analyze a series of advertisements, videos and images on social media, where sports activities are represented as a model or example of the new individual and female body ideal.